Effectiveness and safety of oral nutrition in older patients with moderate dysphagia: a real-world cohort study in geriatric inpatients - Mohan Li; Shan Jiang; Jiaojiao Li; Xiling Chen; Lan Ma; Qihao Guo; Yuehui Wang; Lan Luo; Liping An; Yonghua Wu; Wei Huang; Ludan Yuan; et al. (BMC Geriatrics)
Abstract Background Dysphagia and malnutrition increase with age and are correlated with adverse clinical outcomes. Researchers have not fully studied the safety and effectiveness between oral nutrition pathway and tube feeding in dysphagic and malnourished elderly individuals. Methods Elderly individuals > 65 years old with nutrition risk admitted to the department of geriatrics from 58 third-grade hospitals between September 2020 and December 2022 were recruited. The analysis was conducted in patients with moderate dysphagia. Baseline characteristics, including demography, nutrition, swallowing function and body function, were collected per inclusion. Nutritional suggestions were given by geriatricians and nutritionists. Nutritional therapy pathways were recorded, and the body and functional measurements were repeated at discharge and the 90-day follow-up. Adverse outcomes, including new-onset pneumonia, falls, unplanned readmission and all-cause death were recorded. Results A total of 1027 hospitalized elderly individuals were included, with 168 (16.4%) having moderate dysphagia. Among the participants receiving oral nutrition or tube feeding, 91 (81.3%) and 45 (80.4%) gained sufficient calories after nutritional intervention and were included in the analysis. The median age was 89 (IQR: 82–92) years, 43 (31.6%) were female, and 128 (94.1%) were malnourished. Ninety-one (66.9%) patients were treated with oral nutrition (oral diet or oral nutritional supplements), and 45 (33.1%) were treated with tube feeding. Among the oral nutrition patients, 11 (12.1%), 3 (3.3%), 14 (16.7%) and 2 (2.6%) had new-onset pneumonia, all-cause death, readmission and falls, respectively. The corresponding events in the tube-feeding group were 5 (11.1%), 1 (2.2%), 7 (16.7%) and 1 (2.5%). No statistically significant difference was observed between nutrition treatment pathways. BMI, grip strength and calf circumference increased similarly between the oral nutrition and tube-feeding groups, whereas the percentage of improved MNA-SF status was greater in the oral nutrition group than in the tube-feeding group (53% vs. 26%, p = 0.004). Conclusions Among moderately dysphagic geriatric inpatients with malnutrition or nutritional risk, oral nutritional may demonstrate comparable safety to tube feeding regarding new-onset pneumonia, all-cause death, readmissions, and falls during short term follow-up. Oral nutrition may also demonstrate comparable effectiveness in terms of energy supply and improving function, and oral nutrition may be more effective in improving nutritional status. Trial registration ClinicalTrials.gov: NCT04751032.